2018
DOI: 10.1016/j.jtrangeo.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Does commuting matter to subjective well-being?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 60 publications
7
44
2
Order By: Relevance
“…By contrast to Stutzer and Frey (2008), Lorenz (2018) found no association between commute distance and life satisfaction using the same data source and method but data for years 2007-2013. In the UK context, no association was found between commute time and life satisfaction in a fixed effects regression analysis of data from 1996 to 2008 for participants of the British Household Panel Survey (BHPS) (Dickerson et al 2014).…”
Section: Commuting and Satisfaction With Life Overallcontrasting
confidence: 67%
See 3 more Smart Citations
“…By contrast to Stutzer and Frey (2008), Lorenz (2018) found no association between commute distance and life satisfaction using the same data source and method but data for years 2007-2013. In the UK context, no association was found between commute time and life satisfaction in a fixed effects regression analysis of data from 1996 to 2008 for participants of the British Household Panel Survey (BHPS) (Dickerson et al 2014).…”
Section: Commuting and Satisfaction With Life Overallcontrasting
confidence: 67%
“…Cross-sectional studies have shown longer commute times associated with reduced happiness (Olsson et al 2013;Choi et al 2013;ONS 2014;Nie and Sousa-Poza 2018). However, Lorenz (2018) found no association between commute distance and frequency of feeling angry, worried, happy or sad (based on panel data and fixed effects models for workers in Germany). It is unclear whether these contrasting results might be explained by differences in exposure measures used (commute time versus distance) or differences in the data and type of analysis used (cross-sectional data/analysis versus longitudinal data/analysis).…”
Section: Commuting and Satisfaction With Sub-domains Of Lifementioning
confidence: 98%
See 2 more Smart Citations
“…The impact of long commuting on the daily life of urban residents is becoming more and more obvious. Excessive commuting time can lead to physical and mental exhaustion [43,44], which can affect work efficiency and shorten the time for family life. Moreover, people of different social classes differ significantly in their modes of commuting and time spent commuting.…”
Section: Commuting Affects Perceptions Of Social Equity In Urban Chinamentioning
confidence: 99%